2023
DOI: 10.54905/disssi/v27i135/e206ms2985
|View full text |Cite
|
Sign up to set email alerts
|

Perception, awareness and attitude towards varicose veins among employees working in prolonged sitting and standing postures in Hail region, Saudi Arabia

Fahmida Khatoon,
Sadeem Mishaal Mohammad Alshammari,
Nawal Ahmed Alshammari
et al.

Abstract: Background: One of the most common chronic conditions is varicose veins (VV), which contribute to a higher rate of morbidity as different symptoms can result from varicose veins ranging from itching to ulceration. Aim of this study is to assess the level of knowledge and attitude towards Varicose and treatment methods among the population of Hail in Saudi Arabia. Methods: A well-defined questionnaire was conceded among the general population over-18-year-old men and women are the study's subjects. To gauge pub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
(17 reference statements)
1
0
0
Order By: Relevance
“…As for diagnostic methods, study participants showed inappropriate knowledge and awareness levels where Doppler US was known for only one-fourth of them. In Hail, Khatoon et al found that disease pathophysiology and risk factors are well known among 46% of the study group and less known by 56.0% of the study population only [14]. Also, George et al found that the majority of respondents (70%) had a moderate level of knowledge which is similar to the current study findings [15].…”
Section: Discussionsupporting
confidence: 86%
“…As for diagnostic methods, study participants showed inappropriate knowledge and awareness levels where Doppler US was known for only one-fourth of them. In Hail, Khatoon et al found that disease pathophysiology and risk factors are well known among 46% of the study group and less known by 56.0% of the study population only [14]. Also, George et al found that the majority of respondents (70%) had a moderate level of knowledge which is similar to the current study findings [15].…”
Section: Discussionsupporting
confidence: 86%